2020
DOI: 10.3389/fpsyg.2020.567966
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 Coronavirus Pandemic as a Change-Event in Sport Performers’ Careers: Conceptual and Applied Practice Considerations

Abstract: The Coronavirus experience (CE) presents a highly challenging period for sport performers (e.g., athletes, coaches, referees), with potential effects on their lives and career trajectories. In this article, we initially conceptualize the CE using the scheme of change for sport psychology practice (Samuel and Tenenbaum, 2011a). Within this framework, the CE is understood as a longitudinal, multifaceted, unpredicted, non-controlled change-event, with four distinct stages: (a) a pre-Coronavirus stage with unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 38 publications
5
95
0
5
Order By: Relevance
“…Within the sports field, previous evidence relates mental health issues with higher difficulties to undertake a dual career pathway (Sallen et al, 2018;Sorkkila et al, 2020). As highlighted by other authors (e.g., Samuel et al, 2020;Stambulova et al, 2020), COVID-19 lockdown can be understood as a changeevent with unexpected demands for the athletes that combine academic and sports career. Therefore, it would be interesting that future research addresses the impact of this adaptation process on young athletes' mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the sports field, previous evidence relates mental health issues with higher difficulties to undertake a dual career pathway (Sallen et al, 2018;Sorkkila et al, 2020). As highlighted by other authors (e.g., Samuel et al, 2020;Stambulova et al, 2020), COVID-19 lockdown can be understood as a changeevent with unexpected demands for the athletes that combine academic and sports career. Therefore, it would be interesting that future research addresses the impact of this adaptation process on young athletes' mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Research addressing the impact of this pandemic in sports identified specific challenges for athletes’ mental health during the lockdown, such as the difficulty in keeping training conditions ( Pillay et al, 2020 ), the social distancing from teammates ( Graupensperger et al, 2020 ), and the uncertainty regarding the delay or cancelation of future competitions ( Samuel et al, 2020 ). Despite most of these challenges are common for athletes of all ages and levels, research has mainly focused on high performance, professional, and/or Olympic/Paralympic athletes (see also Schinke et al, 2020a , b ; Stambulova et al, 2020 ), letting youth sports’ reality underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a specific conceptual model proposal has recently appeared [“Coronavirus Experience,” CE, ( 74 )] that is based on their previous Scheme of change for sport psychology practice model ( 75 ) that is not far from the model of response to sports injuries. CE is defined as an unpredictable, longitudinal, and multifaceted change event that consists of three phases: phase A, characterized by instability and confusion, emotional response, and appraisal; phase B, defined by coping and regression; and phase C, in which instability can increase or decrease depending on the previous sporting trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…This would entail the development of novel training modalities, in addition to existing VAR simulators, so referees can continue independent practice. New online options, such as Zoom-based training (see Samuel et al, 2020c), can be exploited for this purpose. Analyzing the refereeing team communication in critical match incidents is of high importance.…”
Section: Practical Recommendationsmentioning
confidence: 99%